Crises unwasted: how policy entrepreneurs linked forest biomass to energy security in Colorado, 1998-2013 - Eckhoff, Mike, author; Mackes, Kurt, advisor; Knight, Rick, advisor; Davis, Charles, committee member; Fiege, Mark, committee member; Patton-Mallory, Marcia, committee member; Rideout, Douglas, committee member (Colorado State University. Libraries, 2014)
Colorado's forests are facing threats from wildfires, insect and disease epidemics and human encroachment. At the same time, Coloradans are facing energy security problems from fossil fuel price volatility, unintended consequences from continued fossil fuel dependence, problematic alternative, non-renewable fuel promotions and a struggling renewable energy industry. Subsequently, natural resources managers in Colorado are facing two imposing challenges simultaneously: 1) the need to restore forest health and 2) to manage energy resources sustainably, equitably and with public safety in mind. Policy entrepreneurs invested in forest energy found ways to link forest health emergencies to energy security crises. This dissertation is a study that explores how that link was forged and what happened in Colorado as result, looking at the actions taken by the four major federal land management agencies (U.S. Forest Service, Bureau of Land Management, National Park Service and the U.S Fish and Wildlife Service). This study also traced briefly how the State of Colorado responded to these crises, too. First, this study qualitatively surveyed literature in the forest history and policy arenas and energy history and policy arenas to chart how prior events led to current conditions. Media articles were tabulated and coded to quantitatively gauge how salient their respective issues were over time. Using Multiple Streams Theory, policy windows were identified. Second, the Punctuated Equilibrium Theory was applied to the emerging forest energy policy arena during the time frame identified by the policy windows. Finally, interviews and meetings were held with employees at the federal, regional/state and local levels and with members of state government to determine how the increased saliency of forest and energy issues translated to forest energy policy actions on the ground in Colorado. This dissertation concludes that federal land management agencies took greater interest and made significant efforts to promote forest energy in Colorado between the years 2000 and 2013. This increased interest resulted in increased funding, regulation and project development and implementation in the state. However, while activity increased, opportunity for additional actions remains. Coloradans would be wise to foster additional public-private initiatives and work to promote forest energy among large groups of proximal forest communities. Inevitably, as fossil fuel supplies decrease and prices increase, Colorado, along with the rest of the country, will in part be forced to return back to its "roots" and Dukert's notion of "the future behind us."
Keywords: fossil fuels; policy; renewable; thermal; wildfire; punctuated equilibrium theory